PROFITABILITY ANALYSIS OF TERUBUK FARMING (SACCHARUM EDULE HASSKARL) IN SUBDISTRICT TOSA DISTRICT OF EAST TIDORE OF TIDORE ISLAND - Suwandi S. Sangadji (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this researchment is to ascertain how wide the farming of species Saccharun Edule Hasskarl (terubuk) in sub district Tosa, district of East Tidore of Tidore Island through the indicator of the value revenue, production and selling prices so that the farmers will achieve The Break Event Point (BEP). The research method was used a quantitative method with the number of samples of 30 people. The determination of the sample method is using the census method or involving all members of the population into a sample of researchment. The secondary data collection was done by using library literature in the form of document review and relevant references to research object while primary data collection was done by using questionnaire. The data is using equation R /C Ratio, BEP Revenue, BEP Price, and BEP Production. Therefore from the results of the researchment it can be explained that the two of the thirty farmers come through the break event point, while the other twenty-eight farmers declared having a business that worth to be develop or experiencing profit, because the R/C ratio is above 1.0 with average profit reach Rp. 989.000, - per production / farmer. Keywords: Profitability, Terubuk Farming